Enthousiasme et désenchantement - Mireille Lalancette; Frédérick Bastien (Communication)
Unlike the literature that focuses on the use politicians make of digital technology, this study adopts the perspective of the citizens targeted by their campaigns. It examines their expectations and their assessment of the digital campaigns led by Québec’s political parties in the run‑up to the province’s 2012 election. The study combines the results of an online survey with a qualitative analysis of focus groups. The results point to the existence of a predominantly informational motivation and a disillusionment on the part of citizens regarding the use parties and candidates make of digital technologies, particularly the lack of dialogue and authenticity.